Atypical antipsychotics: A review on the prevalence, monitoring, and management of their metabolic and cardiovascular side effects - Wei Xin Chong, Joyce (Ment Health Clin, 2016)
INTRODUCTION: Excessive weight gain, glucose intolerance, and dyslipidemia are well-known physical side effects of the metabolic syndrome commonly associated with atypical antipsychotic (AAP) treatment. We review these side effects of AAPs and their monitoring and management strategies. METHODS: A literature search was conducted to identify articles published on the prevalence, monitoring, and management of cardiometabolic side effects of AAPs. RESULTS: Comparative risk of AAPs on weight gain, hyperlipidemia, glucose intolerance, and QT interval corrected for heart rate prolongation varies across the AAPs currently available. Likewise, pharmacologic and nonpharmacologic options investigated for management of these side effects, and monitoring those at appropriate intervals, differ based on the clinical condition and risk factors identified. DISCUSSION: Atypical antipsychotics in general have little difference among them in short-term efficacy; however, the prevalence of their physical side effects substantially distinguishes them. It is of importance that clinicians carefully select AAPs bearing in mind the presence of risk factors, initiating patients directly on AAPs with a low risk of cardiometabolic side effects, and monitoring and managing those side effects at appropriate intervals.